Analisis Kurikulum Melalui Model Pendekatan Humanistik Di MA Muallimat Muhammadiyah - Islamiyah Nur Hidayati; Chandra Intan Berliana; Aditya Putra Mahardhika; Gaidha Lutfi Fadzilatunnisa; Muhammad Zaki Firman Ilhami; Badrus Zaman (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2024)
This research examines the implementation of a humanistic approach-based curriculum at Madrasah Aliyah (MA) Muallimat Muhammadiyah, founded on the personal education theories of John Dewey and J.J. Rousseau. Using qualitative methods through interviews and observations, this study analyzes the application of the humanistic approach in the madrasah curriculum. The research findings reveal that the curriculum implementation not only focuses on academic aspects but also encompasses students' moral and social development through various integrative learning activities. The research identifies three main findings: First, the integration of academic subjects between religious education and science that produces comprehensive understanding for students. Second, social reconstruction manifested through students' active involvement in identifying and solving social problems in their environment. Third, the effective utilization of technology to enrich the learning process and develop students' digital capabilities. The humanistic approach in the curriculum proves effective in developing students holistically. This is evident from the improvement in academic achievement balanced with mature personality development and good social skills. These findings indicate that the humanistic approach can serve as an ideal curriculum development model for Islamic educational institutions in preparing a generation that is not only intellectually intelligent but also possesses strong character.